Actividades culturales del turismo y equidad social en la comunidad Rumicruz, parroquia Calpi, cantón Riobamba - Samaniego Carrazco, Edwin Rolando (2025)
The aim of this research “Cultural Activities of Tourism and Social Equity in Rumicruz community, Calpi parish, Riobamba canton” is to analyze the relationship between cultural activities of tourism and social equity in Rumicruz, because this parish has a great cultural identity based on its knowledge, wisdom, manifestations and ancestral expressions which gives it a very high cultural value but in recent years has been threatened by various factors such as globalization, culturalization and others. Furthermore, being a qualitative research, the research methods chosen were non- experimental and transversal, taking information from the field as well as documented, working hand in hand with the inhabitants of Rumicruz community, who were also part of the study sample, with an estimated 30 people surveyed based on the Likert scale in order to analyze the cultural tourism activities that can be carried out, thus achieving an organization and union of the community. . However, through the responses of the surveyed people, it is possible to see the great value that still exists for their ancestral traditions and despite the fact that these are vulnerable in today's society, there is a predisposition of both the inhabitants and the tourism actors to preserve this tradition. Finally, a brief proposal is presented in order to design a cultural tourism product for the community.